2007
DOI: 10.1016/j.ijrobp.2006.12.068
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Image Registration and Intensity-Modulated Radiotherapy Planning With Hyperpolarized Helium-3 Magnetic Resonance Imaging for Non–Small-Cell Lung Cancer

Abstract: Purpose: To demonstrate the feasibility of registering hyperpolarized helium-3 magnetic resonance images (3He-MRI) to X-ray computed tomography (CT) for functionally weighted intensity-modulated radiotherapy (IMRT) planning.Methods and Materials: Six patients with non–small-cell lung cancer underwent 3He ventilation MRI, which was fused with radiotherapy planning CT using rigid registration. Registration accuracy was assessed using an overlap coefficient, calculated as the proportion of the segmented 3He-MR vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 25 publications
3
87
1
Order By: Relevance
“…Seven scenarios using simulated functional imaging data representing locally advanced NSCLC have demonstrated that inclusion of functional information in IMRT plan optimisation allowed improved avoidance of functional lung, as assessed by FV 20 and the MFLD, compared to anatomical IMRT alone. The median reduction in FV 20 of 2.7% demonstrated in this simulation study is in keeping with that observed previously by Ireland et al of 3.1% (range 0.4-5.1%) [18] when using 3 He-MRI data, although it is less than the 5-6% absolute median reductions in FV 20 observed in selected SPECT literature examining functional versus anatomical IMRT [12,13].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Seven scenarios using simulated functional imaging data representing locally advanced NSCLC have demonstrated that inclusion of functional information in IMRT plan optimisation allowed improved avoidance of functional lung, as assessed by FV 20 and the MFLD, compared to anatomical IMRT alone. The median reduction in FV 20 of 2.7% demonstrated in this simulation study is in keeping with that observed previously by Ireland et al of 3.1% (range 0.4-5.1%) [18] when using 3 He-MRI data, although it is less than the 5-6% absolute median reductions in FV 20 observed in selected SPECT literature examining functional versus anatomical IMRT [12,13].…”
Section: Discussionsupporting
confidence: 91%
“…In addition to improvements in functional lung dose-volume parameters observed in this study, small improvements in total lung V 20 volumes were identified, which have also been found by previous groups investigating functional radiotherapy planning [12,18]. A possible explanation for this improvement in V 20 may be an increased degree of freedom allowed to the planning algorithm when only functional lung doses are constrained, permitting distribution of total lung dose into not only low-dose zones, but also zones of non-functional lung where the 20 Gy threshold has already been exceeded, due to calculation of cost functions in inverse planning via an "area under the curve" method.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It is possible to obtain a 3D volumetric dataset of the lungs using this technique (169), and several authors have shown the utility of this technique in normal volunteers, patients with asthma, emphysema (including alpha-1-antitrypsin deficiency; Figure 10A), cystic fibrosis ( Figure 10B) and lung cancer ( Figure 10C). (170)(171)(172)(173)(174)(175)(176)(177) There is homogeneous ventilation distribution in normal volunteers, although small ventilation defects are frequently seen. (170,(178)(179)(180) In smoking subjects with normal pulmonary function tests, ventilation defects are usually already detectable.…”
Section: Hyperpolarized Gas Imagingmentioning
confidence: 99%